IMPLEMENTASI MANAJEMEN KINERJA DI UNIKA SANTO THOMAS MEDAN - Tinambunan, Anitha Paulina (LPPM Universitas Katolik Santo Thomas Medan, 2024)
The management model of higher education institutions can be equated with a business model of higher education management services that must be managed professionally like other business institutions, but while still prioritizing academic quality as a